Desempenho de sustentabilidade de cooperativas de crédito: um estudo em um sistema cooperativo de crédito brasileiro - Viana, Camila Luconi (Universidade do Vale do Rio dos Sinos, 2016)
Today, although many companies have their own sustainability programs, they still face difficulties in applying its concepts considering their material issues and using sustainability as a driver for perpetuity and shared value creation. The system of credit unions studied in this research, even having a great potential on the theme, also faces this challenge. The goal of this study was to analyze the credit unions’ sustainability performance of a system of credit unions in Brazil through a framework that considers specific attributes on coops. The exploratory study embrace a qualitative and quantitative approach. The social banking/values based banking were set as benchmarks for the improvement of sustainability performance on the credit unions, so the interviews were conducted with three experts to compare them with credit unions. A literature and sustainability guideline review was used to propose a framework for analyzing sustainability performance. Also, to consider credit unions specificities a set of interviews with credit union leaders of the System were used to establish internal benchmarks and to feed the framework proposal. The framework was converted into a questionnaire instrument and applied on a survey to the 95 credit unions of the System. As a result, it was found that, contrary to what the literature argues, credit union is just a legal form if their values are not practiced. There is a strong adherence of credit unions to the principles of social banks/values based banks, but requires focus on the use of financial resources to stimulate activities that promotes positive social and environmental impact. In the framework were suggested the following constructs: business model, governance and economic performance, products and services, environmental and social. Also, specifically linked subconstructs to the credit unions was suggested: democratic management, local development, members training and regional coordination/intercooperation. Finally, the average performance of the 34 cooperatives was 2.64 and a median of 2.69, which shows that credit unions have random actions in relation to sustainability and that it is necessary to adopt indicators and formal management processes. The latest processes related to sustainable development presented the greatest opportunity for improvement. The highest performance constructs were governance and economic and social construct, which are the basic pillars of a credit union. The implications of this results for the System is that it is necessary to set an ambition for sustainability strategy to improve the results, mainly by defining indicators, measuring and establishing processes to improve them.
Keywords: Sustentabilidade; Cooperativismo de crédito; Instituições financeiras sustentáveis; Bancos sociais; Bancos baseados em valores; Desempenho em sustentabilidade; Sustainability; Credit union; Sustainable financial institution; Social banking; Values based banking; Sustainability performance; ACCNPQ::Ciências Sociais Aplicadas::Administração